Physics of Moses’ Exodus, of vampire myths, of family structures, of modern ideologies, and of the celiac disease - Pirot, Florent (European Journal of Applied Sciences, 2021)
Alpha-emitting nanoparticulates, relativistic neutrons and other principles of physics brought together allow to confirm many elements in the Ancient Testament (in particular the Exodus, in addition to what was already shown in earlier works of the author), the birth of the “vampire” concept in the 19th Century, to explain the existence of various family structures (as underlined by the Leplaysian school, and more recently by Emmanuel Todd), and the emergence of modern ideologies, by underlining the major forces at work under the maps in L’Invention de l’Europe and L’Origine des systèmes familiaux. The celiac disease is also included as a case study where alpha-emitting nanoparticulates, as usual in noncommunicable diseases, are the key factor but where a very specific medical reply is required.